2016
DOI: 10.1140/epjc/s10052-016-4117-6
|View full text |Cite
|
Sign up to set email alerts
|

Quark flavor mixings from hierarchical mass matrices

Abstract: In this paper, we extend the Fritzsch ansatz of quark mass matrices while retaining their hierarchical structures and show that the main features of the CabibboKobayashi-Maskawa (CKM) matrix V , including |V us | |V cd |, |V cb | |V ts | and |V ub |/|V cb | < |V td |/|V ts |, can be well understood. This agreement is observed especially when the mass matrices have non-vanishing (1, 3) and (3, 1) offdiagonal elements. The phenomenological consequences of these for the allowed texture content and gross structura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 102 publications
1
23
0
Order By: Relevance
“…In particular, a fine tuning of the free parameters in terms of the quark masses yields interesting predictions in certain texture possibilities as well as retain strongly hierarchical structures for quark mass matrices discussed in [77]. In principle, it is concluded that in addition to Fritzsch-like texture four zeros, several viable structures for hierarchical quark mass matrices involving symmetric texture zeros may be compatible with current precision data, with certain structures being sensitive to light quark masses and all such structures [40] may not yield interesting predictions as obtained in the Cases discussed above.…”
Section: Results and Conclusionmentioning
confidence: 96%
“…In particular, a fine tuning of the free parameters in terms of the quark masses yields interesting predictions in certain texture possibilities as well as retain strongly hierarchical structures for quark mass matrices discussed in [77]. In principle, it is concluded that in addition to Fritzsch-like texture four zeros, several viable structures for hierarchical quark mass matrices involving symmetric texture zeros may be compatible with current precision data, with certain structures being sensitive to light quark masses and all such structures [40] may not yield interesting predictions as obtained in the Cases discussed above.…”
Section: Results and Conclusionmentioning
confidence: 96%
“…In [26], the authors extended this formalism for scalar fields with tachyonic dynamics. Recently, Moraes and Santos [27] presented a cosmological picture in ( , ) gravity in the absence of matter by considering flat FRW model. They started with the relatioṅ= − / which comes from the field equations of GR via the abovementioned formalism.…”
Section: Introductionmentioning
confidence: 99%
“…We have applied this formalism to Bianchi type-I universe model (with no matter present) and concluded that the exponential form of ( ) can explain all the stages of the universe evolution [28]. The motivation for neglecting matter action is that ( , ) framework cannot describe the radiation-dominated era because in that phase the value of for perfect fluid is zero and ( , ) theory is reduced to ( ) scenario [27]. Moreover, Alves et al [20] showed that for gravitational wave passing through vacuum with no extra polarization modes are induced due to curvature matter coupling as = 0 in vacuum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations [4] in this regard indicate that the current quark mixing data indeed permit the quark mass matrices to have such a natural and hierarchical structure provided ( ) ∼ ( √ ) for , = 1, 2, 3, ̸ = and ( ) ∼ ( ). Such hierarchical mass matrices have been referred to as natural mass matrices [5].…”
Section: Introductionmentioning
confidence: 99%